2012
DOI: 10.1007/s12010-012-9701-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Bacteriocin-Producing Lactococcus lactis and Application of Its Bacteriocin to Manage Spoilage Bacteria in High-Value Marine Fish Under Different Storage Temperatures

Abstract: The bacteriocins of lactic acid bacteria have considerable potential for biopreservation. The Lactococcus lactis strain PSY2 (GenBank account no. JF703669) isolated from the surface of marine perch Perca flavescens produced antibacterial activity against pathogenic and spoilage-causing Gram-positive and Gram-negative bacteria viz. Arthrobacter sp., Acinetobacter sp., Bacillus subtilis, Escherichia coli, Listeria monocytogenes, Pseudomonas aeruginosa and Staphylococcus aureus and possessed broad inhibitory spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…The pH of fish flesh is frequently observed to increase during chilled storage (Gildberg, 1978;Ruff et al, 2002;Sarika et al, 2012). This can be attributed to the production of volatile bases by bacteria within the tissues as glycogen is utilised as an energy source, as well as to the actions of heterofermentative lactic acid bacteria which grow and degrade amino acids with the formation of carbon dioxide and other decarboxylation products (Sarika et al, 2012). In this study, we observed increases in pH in whole ungutted fish whilst the pH of filleted fish remained stable and appeared to decrease in unenriched fillets during storage.…”
Section: Discussionmentioning
confidence: 99%
“…The pH of fish flesh is frequently observed to increase during chilled storage (Gildberg, 1978;Ruff et al, 2002;Sarika et al, 2012). This can be attributed to the production of volatile bases by bacteria within the tissues as glycogen is utilised as an energy source, as well as to the actions of heterofermentative lactic acid bacteria which grow and degrade amino acids with the formation of carbon dioxide and other decarboxylation products (Sarika et al, 2012). In this study, we observed increases in pH in whole ungutted fish whilst the pH of filleted fish remained stable and appeared to decrease in unenriched fillets during storage.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for a possible use in fishery products, bacteriocins would be more adapted to the substrate (Calo-Mata et al, 2008). However, the study of the use of bacteriocins as fish preservatives has been focused on their antilisterial activity and not in their ability to control the growth of spoilage bacteria or their combined use with other antimicrobials (Sarika, Lipton, Aishwarya, & Dhivya, 2012;Vescovo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…17 Psychrophilic bacteria limitation in fish fillet is 7 logCFUg -1 . 19 According to results of day 15, in 2% treatment of immersion method and control until day 15 the number of psychrophilic bacteria exceeded from 7log CFUg -1 that were 7.31±0.03, 7.51±0.22 logCFUg -1 , respectively (Figure 1). In samples with 4% supernatant and live cells with concentration of 6log CFUg -1 , the number of psychrophilic bacteria on 15th day were 5.36±0.09, 4.25±0.06 logCFUg -1 , respectively ( Figure 1) that were less than human consumption limit.…”
Section: Discussionmentioning
confidence: 93%
“…2%, 4% solutions of this supernatant were prepared using distilled water. [13][14][15][16][17][18][19][20][21] Pure bacteria of lactic acid bacteria preparation Serial dilutions were prepared and then pour plated in solid nutrient broth culture, made by Merck Co. Germany, medium and incubated in 30°C to count the grown colonies after 48 hours and stored in the refrigerator to avoid the further growth of bacteria during the colony counting and the initial concentration of our solution were obtained. Concentration of 10 6 ml -1 were prepared that in this work we call it live cells or pure bacteria of L. lactis subsp.…”
Section: Bacterial Preparation and Supernatants Extractionmentioning
confidence: 99%
See 1 more Smart Citation